Criteria for the formation of creative competence in students in technology lessons - Saidnazarova To’lganoy Makhmudovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
this article describes the acquisition of knowledge, skills, and abilities necessary for the implementation of professional competence of students of grades 5-9 of future teachers of technological education and methods of their practical application.